Single Performance Optimization of Micro Metal Injection Molding for the Highest Green Strength by Using Taguchi Method - Ibrahim, M.H.I; Muhamad, N.; Sulong, A.B; Jamaludin, K.R.; Ahmad, S.; Nor, N.H.M (International Journal of Integrated Engineering, 2010)
Micro metal injection molding is drawing attention recently as one the most cost effective processes in powder metallurgy to produce small-scale intricate part and competitive cost for mass production of micro components where it is greatly influenced by injection parameter. Thus, this paper investigated the optimization of highest green strength which plays an important characteristic in determining the successful of micro MIM. Stainless steel SS 316L was used with composite binder, which consists of PEG and PMMA while SA works as a surfactant. Feedstock with 61.5% with several injection parameters were optimized which highly significant through screening experiment such as injection pressure(A), injection temperature(B), mold temperature(C), injection time(D) and holding time(E). Besides that, interaction effects between injection pressure, injection temperature and mold temperature were also considered to optimize in the Taguchi’s orthogonal array. Analysis of variance (ANOVA) in terms of signal-to-noise ratio (S/N-larger is better) for green strength was also presented in this paper. Result shows that interaction between injection temperature and mold temperature (BxC) give highest significant factor followed by interaction between injection pressure and injection temperature (AxB). Single factor that also contributes to significant optimization are mold temperature(C), injection time (D) and injection pressure (A). Overall, this study shows that Taguchi method would be among the best method to solve the problem with minimum number of trials.